2015
DOI: 10.1038/srep15057
|View full text |Cite|
|
Sign up to set email alerts
|

Functional identification of SLC43A3 as an equilibrative nucleobase transporter involved in purine salvage in mammals

Abstract: The purine salvage pathway plays a major role in the nucleotide production, relying on the supply of nucleobases and nucleosides from extracellular sources. Although specific transporters have been suggested to be involved in facilitating their transport across the plasma membrane in mammals, those which are specifically responsible for utilization of extracellular nucleobases remain unknown. Here we present the molecular and functional characterization of SLC43A3, an orphan transporter belonging to an amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 28 publications
4
42
0
Order By: Relevance
“…Dipyridamole, a potent inhibitor of both ENT1 and ENT2, has no effect on cellular [ Human ENBT1/SLC43A3 is expressed abundantly in the liver, lung, and heart, and ubiquitously in the pancreas, testis, thymus, placenta, and kidney. 10,48) Immunohistochemical studies showed that ENBT1/SLC43A3 is localized on the sinusoidal membrane of human hepatocytes 10) and on the basolateral membrane of epithelial cells of the proximal convoluted tubule in the human kidney. 48) Consistent with those results, GFPtagged ENBT1/SLC43A3 is localized on the basolateral membrane of polarized MDCKII cells.…”
Section: Enbt1/slc43a3mentioning
confidence: 99%
See 4 more Smart Citations
“…Dipyridamole, a potent inhibitor of both ENT1 and ENT2, has no effect on cellular [ Human ENBT1/SLC43A3 is expressed abundantly in the liver, lung, and heart, and ubiquitously in the pancreas, testis, thymus, placenta, and kidney. 10,48) Immunohistochemical studies showed that ENBT1/SLC43A3 is localized on the sinusoidal membrane of human hepatocytes 10) and on the basolateral membrane of epithelial cells of the proximal convoluted tubule in the human kidney. 48) Consistent with those results, GFPtagged ENBT1/SLC43A3 is localized on the basolateral membrane of polarized MDCKII cells.…”
Section: Enbt1/slc43a3mentioning
confidence: 99%
“…48) This issue was resolved by a study attempting to identify the cDNA of a purine nucleobase transporter using comprehensive functional screening, in which human SLC43A3 was found to stimulate the accumulation of [ 3 H] adenine in HEK293 cells. 10) Currently, SLC43A3 is considered to be a molecular entity of the facilitative purineselective nucleobase transport system involved in the uptake of adenine and hypoxanthine in many types of cells. ] adenine uptake occurs when ENBT1/SLC43A3 is introduced in mouse fibroblast-derived A9 cells that lack the capability to salvage purine nucleobases.…”
Section: Enbt1/slc43a3mentioning
confidence: 99%
See 3 more Smart Citations